Septic Shock on Bartholinitis: Case Report and Modern Surgical Approaches - Fakir, Oumaima; Lazhar, Hanaa; Slaoui, Aziz; Lakhdar, Amina; Baydada, Aziz (Clinical Journal of Obstetrics and Gynecology, 2025)
Bartholinitis, or Bartholin's gland abscess, is a relatively common gynecological condition among women of reproductive age. Its annual incidence is estimated at approximately 0.5 per 1,000 women, which corresponds to a lifetime cumulative risk of about 2%. The condition primarily affects patients between 20 and 50 years old, with a peak frequency observed between 35 and 50 years. After menopause, due to the natural involution of the gland, Bartholin's cysts and abscesses become less frequent, although they can still occur. Moreover, in women over 50, the appearance of a new mass in the gland region should prompt caution, as it may, in rare cases, indicate a carcinoma of the Bartholin's gland or an adjacent vulvar cancer. Therefore, for patients over 40 presenting with a newly emerged cyst or abscess, clinical guidelines recommend performing a biopsy or excision to rule out malignancy. We present the case of a 50-year-old woman with no significant medical history, who was urgently referred to the gynecological emergency department due to confusion, unexplained fever of 40 °C, and resistant leucorrhoea following a week of corticosteroid antibiotic therapy. Clinical examination revealed a large, tender right vulvar mass, indicative of an acute Bartholin's abscess. The patient exhibited signs of septic shock and was admitted to the ICU. Following a diagnosis of sepsis, broad-spectrum antibiotic therapy was initiated, alongside fluid resuscitation and norepinephrine support. Surgical drainage of the abscess confirmed the presence of E. coli. The patient's condition improved rapidly, and she was discharged on postoperative day 8 with no complications. This case underscores that while Bartholin's abscess is typically benign, severe complications, including septic shock, can occur—especially in patients over 50. The appearance of a new Bartholin's region mass in older women should prompt consideration of malignancy, necessitating biopsy or excision. Recent studies compare various therapeutic approaches including simple incision and drainage, Word catheter placement, marsupialization, silver nitrate application, and complete gland excision. Each method has its advantages and drawbacks, with marsupialization offering lower recurrence rates and higher patient satisfaction in many instances. Early recognition of severe infection and prompt, aggressive management combining intensive antibiotic therapy and appropriate surgical intervention is crucial to prevent life-threatening complications in Bartholin's abscess, particularly in high-risk, older patients.